Communitarian social demand of the content system in dermatology as a subject for general comprehensive doctors. - Miriam Iglesias León; María Dolores Castillo Menéndez (Medisur)
Our society aspires to develop professionals with some features that establish the image of socialist men, who as patterns, precise the objectives and aspirations that are expected from them reflected in their social role. Today, the teaching activity in the Higher Education is aimed at forming professionals who are able to fulfil with all their functions and to successfully face the problems of production and service with independence and creativeness. This article presents some of the changes carried out in the program of the subject Dermatology with the aim of fulfilling throughout this subject, with the community social demands of the system of knowledge of this discipline for the Comprehensive General Doctor.